Description of fundatrix and sexual morphs of the Asian apricot aphid, Myzus mumecola (Matsumura, 1917) (Hemiptera: Aphididae) - Tomić, Mihajlo; Jovičić, Ivana; Petrović-Obradović, Olivera (Zootaxa, 2024)
Fundatrix and sexual morphs of the Asian apricot aphid, Myzus (Myzus) mumecola (Matsumura, 1917) are described from Serbia with original, clarified slide mounts, and illustrations. The morphological identification of sexual morphs was corroborated through COI barcode sequence analysis. The subgeneric position of this species is discussed and the transfer to subgenus Nectarosiphon is proposed.